Pemanfaatan Media Blog Untuk Meningkatkan Kualitas Hasil Belajar Siswa SMPN 24 Buru di Masa Pandemi Covid-19 - Nanik Indrayani (LP. Ma'arif Janggan Magetan, 2022)
SMPN 24 Buru is a junior high school in the interior of Lolong Guba District, Buru Regency. The location of the SMPN 24 Buru building is in a remote area and has not been able to enjoy internet facilities because it is constrained by the internet network and also the electric light (PLN) which is not normal because it often goes out. The only way that is most appropriate for online learning or better known as face-to-face is through the media of blogs. Students are encouraged to go to neighboring villages that already have internet facilities. By using blog media, the difficulties faced by students in the learning process can be reduced, and students will find it easier to choose and develop their minds in finding new ideas, learning independently and creatively. The general objectives of this research are: 1). Describes the forms of Using Blog Media to Improve the Quality of Student Learning Outcomes of SMPN 24 Buru in the Covid-19 Pandemic Period. 2). Describes the form of using blog media to improve the quality of student learning outcomes at SMPN 24 Buru during the Covid-19 Pandemic. The type of research used in this study uses quantitative research with a correlational research model. This model aims to find out whether or not there is a relationship between the problems studied at SMPN 24 Buru. The location of this research is SMPN 24 Buru which is located in Ukalahin Village, Lolong Guba District, Buru Regency, Maluku. Data collection techniques were carried out through conversational engagement listening techniques, recording techniques, and note-taking techniques. The data that has been classified is then analyzed using qualitative descriptive analysis techniques. The Technology Readiness Level (TKT) in this study consisted of two. The TKT level has several indicators, namely the R&D hypothesis has been prepared, initial data support for the R&D questions to be answered, the R&D design to be carried out has been explored, alternative methodologies, procedures and stages to be carried out have been explored. Based on the two levels of TKT, the type of TKT in this research is Social Humanities and Education.